INJEKSI TRIAMSINOLON EPIDURAL MEMPERBAIKI VISUAL ANALOG SCALE DAN FUNGSI NEUROLOGIS RADIKULOPATI SERVIKAL - Trianggoro Budisulistyo (Neurona Majalah Kedokteran Neuro Sains, 2014)
CERVICAL RADICULOPATHY CR IS A PAIN ANDOR SENSORIMOTOR DEFICIT SYNDROME THAT IS DEFINED AS BEING CAUSED BY COMPRESSION OF A CERVICAL NERVE ROOT THE PAIN IS CAUSED BY COMBINATION OF PINCHING OF THE NERVE ROOT AND INFLAMMATION ASSOCIATED WITH THE DISC MATERIAL ITSELF CORTICOSTEROIDS HAVE THE ACTIONS AS AN ANTIINFLAMMATION STABILIZE NERVE MEMBRANES INHIBITING ECTOPIC IMPULSES INHIBIT ION CONDUCTANCE HYPERPOLARIZE SPINAL NEURONS AND INHIBIT CFIBER TRANSMISSION LIDOCAINE HAS BEEN SHOWN TO HAVE ANTIINFLAMMATORY EFFECT ON NUCLEUS PULPOSUS INDUCED NERVE INJURY BY INCREASE INTRARADICULAR BLOOD FLOW IN AN ANIMAL COMPRESSED NERVE ROOT MODEL INTERLAMINAR EPIDURAL STEROID INJECTION ILESI IS A SAFER EPIDURAL INJECTION PROCEDURE ESPECIALLY ON CERVICAL REGION